TOURISM AND INTERNATIONAL RELATIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Tourism is increasingly recognized as a powerful tool for shaping international relations, and Uzbekistan exemplifies this phenomenon through its strategic embrace of tourism as a cornerstone of its diplomatic and economic strategy. This abstract explores how tourism influences and is influenced by Uzbekistan's international relations, focusing on its role in cultural diplomacy, economic development, and geopolitical positioning. By leveraging its rich cultural heritage and natural assets, Uzbekistan has successfully enhanced its soft power, forged diplomatic ties, and contributed to regional stability. Looking ahead, Uzbekistan’s tourism sector is poised for continued growth, driven by diversification, digital transformation, and sustainable practices, further solidifying its role as a key player in Central Asia’s evolving geopolitical landscape.